Quality of Elementary School Graduates : The Contribution of Teacher Leadership, Student Self-Regulated Learning, and School Culture - Indra Juharni; Suyatno Suyatno; Widodo Widodo; Nunu Nurfirdaus; Deprizon Deprizon (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research aims to analyze the factors that influence the quality of elementary school graduates. Potential contributors were examined as teacher leadership, student self-regulation, and school culture. The method used is correlational research with a quantitative approach. One hundred forty-seven elementary school teachers in Bantul Regency were given a questionnaire to assess the pre-requisites. This data was then used for a multiple linear regression analysis using the SPSS version 22. The results showed a significant influence of teacher leadership, student self-regulated learning, and school culture on the quality of graduates. Teacher leadership and student self-regulated learning were the two most important factors influencing quality. Additionally, school culture was found to have a partial, significant influence on the quality of graduates. Therefore, improving teacher leadership, student self-regulated learning, and school culture in education help upgrade graduates' quality.